Analisis Eksperimental Pengaruh Groundstrap terhadap Torsi dan Daya Mesin Sepeda Motor 4-Langkah - Yonas To; Priyono Priyono; Wofrid Erlista Bianome; Damianus Manesi (CV. IRA PUBLISHING, 2025)
This study aims to analyze the effect of groundstrap installation on motorcycle torque and power. The ground strap, a copper wire coil wrapped around the ignition coil cable, functions to suppress stray frequencies, stabilizing the current flow to the spark plug for optimal combustion. The experiment involved three conditions: standard (no groundstrap), a 0.20 mm groundstrap, and a 0.18 mm groundstrap. Results showed improved performance with both groundstrap configurations. Maximum power increased from 9.16 HP (standard) to 9.30 HP (0.20 mm) and 9.33 HP (0.18 mm). Maximum torque rose from 9.76 N.m to 9.96 N.m (0.20 mm) and 10.09 N.m (0.18 mm). The most significant improvement was achieved with the 0.18 mm groundstrap, yielding an additional 0.17 HP at 7,336 RPM and 0.33 N · m at 6,000 RPM. These findings indicate that groundstrap installation positively affects ignition stability and combustion efficiency, offering a simple yet effective solution to enhance engine performance.